Zero-valent iron core–iron oxide shell nanoparticles coated with silica and gold with high saturation magnetization. Issue 97 (22nd November 2021) - Mehdipour, Milad; Gloag, Lucy; Lian, Jiaxin; Tilley, Richard D.; Gooding, J. Justin
Abstract : A new type of gold-coated magnetic nanoparticle with strongly magnetic zero-valent iron core–iron oxide shell were synthesized. Abstract : A new type of gold-coated magnetic nanoparticle with strongly magnetic zero-valent iron core–iron oxide shell were synthesized. The small size of the magnetic cores and the zero-valent iron ensured superparamagnetic behaviour and high saturation magnetization of the overall nanoparticles. The nanoparticles showed stability against magnetic aggregation and good colloidal stability, which is important for many biomedical applications.